Механизм повышения живучести телекоммуникационной сети путем выбора метрики маршрутизации с использованием теории риска информационной безопасности - Снегуров, А. В.; Чакрян, В. Х. (ХНУРЭ, 2013)
This paper demonstrates the approach of dynamic routing in telecommunication networks, where the elements of the network could be exposed to the influence of potential information security threats. The main concept of the approach is to inject the coefficient that considers the information security level of the route based on factors of network elements survivability. The coefficient is determined based on risk analysis. This allows to consider the influence of routing element failure on network survivability (considering how many links fail if routing element fails) and the probability of successful vulnerability exploitation of this routing element. This analysis allows to determine the most significant routing elements and the most safety route in the network based on the dynamic risks analysis. The goal of the further researches is to evaluate the bandwidth degradation of the links under the influence of the active attack on the routing element, to propose the methods of protection of routing elements and to develop the mechanisms of dynamic routing considering the network survivability and information security.